If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(x + 6 + -5) = 0 Reorder the terms: qrst(6 + -5 + x) = 0 Combine like terms: 6 + -5 = 1 qrst(1 + x) = 0 (1 * qrst + x * qrst) = 0 (1qrst + qrstx) = 0 Solving 1qrst + qrstx = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'qrst'. qrst(1 + x) = 0Subproblem 1
Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing q to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Add '-1x' to each side of the equation. x + -1x = -1 + -1x Combine like terms: x + -1x = 0 0 = -1 + -1x Simplifying 0 = -1 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| y=1/4x^2-9 | | 585+.13x= | | 1/2.9.h=94.5 | | 2+13=30 | | ln(8x^2-5x+1)=0 | | 3x-9=3x-3 | | -196=7x+7(5x+14) | | 525+.21x= | | 1-(1-6m/7) | | (y^2x)*(y^2)-4(y^3)=0 | | 5x-5(4x+31)=-290 | | 43+x=253 | | 3y*3= | | 2(6x-4)=4(5x+3) | | 16y^2-3y+2.25=0 | | log(25x)-log(x-1)=2 | | 360=128+128+52+6x-8 | | -41+4x=79 | | log(b)=0.31 | | 5s+2r+6-3r-2= | | 2(4x-1)=3(3x-5) | | 8(-10x+21)=728 | | -32=0 | | -6c=-6 | | .4*x+150=x | | 180=5x-9+106+33 | | (X^2)*lnx=0 | | 6.25w=68.75 | | 16y^2-3y-16=0 | | -11x-7x+29=-14x+34 | | 3=8x+11+8 | | -7y+17-12y=-38 |